Studies on Nanocrystalline Prussian Blue and its mixed metal analogue for analytical application - Panday, Digvijay (IIT (BHU), Varanasi, 2016)
Abstract is available in the attachment.
This Thesis Submitted by IIT ( BHU ), Varanasi. PhD Scholar and Supervised by - P. C. Pandey
Keywords: Studies; Nanocrystalline; Prussian Blue; Analogue